2005
DOI: 10.3122/jabfm.18.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Postpartum Health Care Utilization and the Effect of Minnesota Early Discharge Legislation

Abstract: Purpose: To describe maternal postdischarge follow-up and health care utilization in the context of Minnesota's early discharge legislation, which mandates coverage for a home visit for a mother and baby who voluntarily leave the hospital early.Methods: Claims data from a large managed care organization were used to identify 22,944 women giving birth from January 1995 through February 1999. Study variables included home or clinic visits within 1 week of discharge (early follow-up), readmissions within 1 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
2
7
1
3
Order By: Relevance
“…This finding contradicts results from other studies [21]; EPNC utilization was driven by postpartum complications in the present study whereas a study in Palestine indicated that EPNC was driven by the number of prenatal care visits and maternal knowledge of postnatal care [16]. Additionally, a prolonged stay in hospital was perceived to reflect perfect health at the time of discharge, and therefore promoted disregard for EPNC.…”
Section: Discussioncontrasting
confidence: 84%
“…This finding contradicts results from other studies [21]; EPNC utilization was driven by postpartum complications in the present study whereas a study in Palestine indicated that EPNC was driven by the number of prenatal care visits and maternal knowledge of postnatal care [16]. Additionally, a prolonged stay in hospital was perceived to reflect perfect health at the time of discharge, and therefore promoted disregard for EPNC.…”
Section: Discussioncontrasting
confidence: 84%
“…Erken taburculuk, herhangi bir komplikasyonun olmadığı durumlarda kadınların vajinal doğumdan 48 saat sonra, sezaryan doğumdan 96 saat sonra taburcu edilmesi olarak tanımlanırken, vajinal doğumdan sonra 24 saat içinde taburcu edilme ise 'çok erken taburculuk' olarak belirtilmiştir (6)(7)(8). Dünya Sağlık Örgütü (DSÖ) ise anne ve yenidoğanın hastane enfeksiyonlarından korunabilmesi için en erken dönemde taburcu edilmeleri gerektiğini bildirmiştir (1).…”
Section: Introductionunclassified
“…Dünya Sağlık Örgütü (DSÖ) ise anne ve yenidoğanın hastane enfeksiyonlarından korunabilmesi için en erken dönemde taburcu edilmeleri gerektiğini bildirmiştir (1). Normal doğumdan 12-48 saat sonra taburcu olunmasını uygun bir süre olarak gören çalışmalar da bulunmaktadır (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionunclassified
“…Las variables relacionadas con egreso temprano en el análisis bivariado (con p<0. 15) fueron incluidas en un modelo de regresión logística. Resultados.…”
Section: Introductionunclassified
“…[1][2][3][4][5][6][7][8][9] Hospital length of stay after childbirth has decreased progressively during the past 60 years. [10][11][12][13][14][15] In the early 1980s in Mexico, the Mexican Social Security Institute (Instituto Mexicano del Seguro Social -IMSS) developed the program Atención de Parto de Bajo Riesgo (Care for Low-Risk Delivery), 16,17 which resulted in a six-hour reduction in postpartum hospital stays.…”
Section: Introductionmentioning
confidence: 99%